PENGEMBANGAN APLIKASI ALARM ANTI-MALING MEMANFAATKAN SENSOR ACCELEROMETER DAN GPS BERBASIS ANDROID - Andy Wongso; Abdul Munir; Hendra Surasa (KHARISMA Tech, 2019)
This research goals is to make an android app that uses accelerometer censor to prevent smartphone gets stolen and to use GPS to find the smartphone if it is getting stolen. The method used on this research is Rapid Application Development (RAD). Benefit of the research is to help preventing smartphone from getting stolen and to find it if it is stolen. This research is started by desigining UML. Then implemented with java using android studio and using firebase as the database. The program is tested using Black box Testing and real life test. According to the results, we can summarize that the writer has been able to design and make an alarm that can secure the phone and track it. Smartphone can and will make a sound if it is moved and can save it last position